A reduced-order model based on finite element method for fast prediction of thermal performance of lattice structures. (July 2021) - Lin, Shengxiang; Cai, Junqi; Xia, Huanxiong; Ao, Xiaohui; Liu, Jianhua
Abstract: Lattice structures, emerging with additive manufacturing technology, have broad application prospects in industry, and desirable thermal and mechanical properties of which can be obtained by changing the internal cells and their array mode. However, the computational cost for the design and analysis of a lattice structure is usually extremely high due to the structural complexity. For fast prediction of thermal performance of lattice structures, a reduced-order model was developed, in which the complex lattice structure is simplified into a three-dimensional rod system and the heat conduction, convection, and radiation are modeled in a reduced second-order way based on the finite element principle. The convergence and accuracy was examined, and the model validation was done by comparing with the corresponding full model. The results showed that the calculation error of the reduced-order model decreases as the rod aspect ratio increases and the computational efficiency is improved by more than 1000 times. The reduced-order model was then applied to evaluate the thermal insulation and thermal dissipation performance of seven kinds of lattice cells, and their characteristics of the thermal performance were found and compared. We finally gave a better designed cell, which shows the best thermal insulation and dissipation performance simultaneously.